Brand Equity. One Perspective Focused on the Accommodation Consumer - Salazar-Duque, Diego Alfredo (2021)
The present work is a review study about the brand value from a perspective centered on the consumer. Its objective was to determine the factors and dimensions of measurement that are required for the construction of brand value with applicability to the lodgings sector. For this research a methodology of qualitative character was considered through documents and bibliographic records elaborated by diverse relevant authors in the subject, which served as a reference for the development in the hotel sector. As a result, variables and measures adaptable to the construction of brand value that could be useful for this type of organization were obtained.